PERLINDUNGAN HUKUM TERHADAP PENGGUNA PINJAMAN UANG ELEKTRONIK SHOPEE PAY LATER - Itok Dwi Kurniawan; Ismawati Septiningsih; Zakki Adihiyati; Kristiyadi Yoke Sarah Asafita (Prodi PPkn Universitas Slamet Riyadi, 2021)
In this millennial era, it is very easy to get an unsecured money loan, one of which is by using a Shopee Paylater electronic money loan. However, in its use it often also causes losses because the interest on the loan is so large that it makes it difficult for users of electronic money loans to pay and pay off their debts. Therefore, this study aims to explore how legal protection is for users of electronic money loans, especially the Shopee Paylater application which is a polemic among the Indonesian people. The method used in this research is a normative legal research method with a conceptual approach and an approach to legislation. The conceptual approach is carried out by analyzing the concept of consumer protection and the agreed agreement to be able to digest the legal relationship between parties in the Shopee application with the Shopee Paylater feature. The results showed that there was a cooperative relationship between Shopee and PT Lentera Dana Nusantara as the lender.